Time to adjuvant chemotherapy and survival in non–small cell lung cancer1. Issue 6 (6th November 2012) - Booth, Christopher M.; Shepherd, Frances A.; Peng, Yingwei; Darling, Gail; Li, Gavin; Kong, Weidong; Biagi, James J.; Mackillop, William J.
Abstract BACKGROUND: The time interval between surgery and initiation of adjuvant chemotherapy (ACT) may impact survival in colorectal and breast cancers. This is the first report describing the association between time to adjuvant chemotherapy (TTAC) and survival in non–small cell lung cancer (NSCLC). METHODS: All cases of NSCLC diagnosed in Ontario, Canada, from 2004 to 2006 who underwent surgical resection (n = 3354) were identified using the Ontario Cancer Registry. TTAC was defined as the interval between dates of surgery and initiation of ACT. Factors associated with TTAC greater than 10 weeks were evaluated by logistic regression. The Cox proportional hazards model was used to describe the effect of delayed TTAC (analyzed as a continuous variable) on overall survival. RESULTS: Among the 1032 cases treated with ACT, the median TTAC was 8 weeks (range, 1‐16 weeks); 35% of cases initiated ACT more than 10 weeks after surgery. Rates of TTAC greater than 10 weeks varied widely across regions (11%‐50%, P = .001). There was no significant association between increased comorbidity and delayed TTAC; there was a trend toward greater delay in TTAC with longer postoperative hospital stay (P = .054) and postoperative readmission to hospital (P = .056). Male sex, higher stage of disease, greater comorbidity, and more extensive surgery were independently associated with inferior survival. TTAC was not associated with overall survival (odds ratio = 1.00, 95% confidence interval = 0.99‐1.00). CONCLUSIONS: One‐third of NSCLC patients treated with ACT in the general population start ACT beyond 10 weeks after surgery. Delayed TTAC does not appear to be associated with inferior survival in NSCLC. Cancer 2013. © 2012 American Cancer Society.